2015
DOI: 10.1039/c5ra20858k
|View full text |Cite
|
Sign up to set email alerts
|

Genetically-enriched microbe-facilitated self-healing concrete – a sustainable material for a new generation of construction technology

Abstract: Genetically modified spore forming B. subtilis bacterial cells for eco-friendly sustainable self-healing bio-concrete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…The characteristics absorption spectrum of the synthesized nanoparticles recorded by spectrophotometer (Figure 6) was a clear evidence of gold nanoparticles where absorption maximum of GNPs was appeared at 523 nm as reported earlier [17]. Our earlier works have shown that one hot spring bacteria isolated from Bakreshwar, West Bengal are able to increase the compressive strength of concrete material when incorporated [10] [11] [18] as well as to synthesis silica nanoparticles from silicate substrate. The bacterium BKH1 is found to secrete a protein (Bioremediase; UniProt Knowledgebase under the accession no.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The characteristics absorption spectrum of the synthesized nanoparticles recorded by spectrophotometer (Figure 6) was a clear evidence of gold nanoparticles where absorption maximum of GNPs was appeared at 523 nm as reported earlier [17]. Our earlier works have shown that one hot spring bacteria isolated from Bakreshwar, West Bengal are able to increase the compressive strength of concrete material when incorporated [10] [11] [18] as well as to synthesis silica nanoparticles from silicate substrate. The bacterium BKH1 is found to secrete a protein (Bioremediase; UniProt Knowledgebase under the accession no.…”
Section: Resultsmentioning
confidence: 82%
“…Samples were then air dried and transferred onto a FESEM alumina supports and sputtered with gold by a coater of Blazers. Slides were observed under FESEM (INSPECT F50 SEM, FEI Europe BV, and Netherlands) and photomicrographs of the bacterial cells were taken in single (40×) magnification [10].…”
Section: Morphology Study By Fesemmentioning
confidence: 99%
See 1 more Smart Citation
“…have been isolated from Bakreshwar hot springs previously, but none of them were found to be highly alkaliphilic as reported earlier (Sarkar et al . , ; Chaudhuri et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…; Sarkar et al . , ). Unfortunately all of those isolated hot spring strains grow at pH 8·0 and survive only for 10–15 days within the cementitious matrices owing to very high alkaline environment.…”
Section: Introductionmentioning
confidence: 99%